Self-Perceived Communication Competence and Its Relationship with Communication Apprehension - Aziz, Sara Alaa Abdul; Faisal, Sanaa Majoul (Journal of Posthumanism, 2025)
Individuals make decisions based on their self-perceived communication competence (SPCC). A person with a high and positive level of SPCC believes in their ability to engage in communication activities, adapt, and manage situations; that is, individuals perceive their communication competence as being dependent on self-awareness rather than on actual communicative ability. Meanwhile, communication apprehension is understood as the fear or anxiety an individual experiences in real or anticipated communication encounters with another person or persons. The present study aims to investigate the following: The level of self-perceived communication competence among gifted students. The level of communication apprehension among gifted students. The relationship between self-perceived communication competence and communication apprehension. The extent to which self-perceived communication competence in its different contexts (talking to strangers, talking to friends, talking to acquaintances, and public speaking) contributes to the overall variance in communication apprehension. To achieve the study’s objectives, the researcher developed a scale for measuring self-perceived communication competence and adopted the Communication Apprehension Scale developed by Al-Naqshbandi (2005). The study sample consisted of 300 male and female students from Gifted Secondary Schools, selected through stratified random sampling from the directorates of education in Baghdad (Al-Rusafa I, Al-Rusafa II, and Al-Karkh II). The researcher established the psychometric properties of the scales, including validity and reliability. The Cronbach’s alpha reliability coefficient for the Self-Perceived Communication Competence Scale was 0.89; in the four contexts, the reliability coefficients were 0.76 for talking to strangers, 0.79 for talking to friends, 0.73 for talking to acquaintances, and 0.76 for public speaking. The Cronbach’s alpha for the Communication Apprehension Scale was 0.86. After analyzing the data using SPSS, the researcher arrived at the following findings: The study sample exhibited self-perceived communication competence. Gifted students experienced communication apprehension. A relationship was found between self-perceived communication competence and communication apprehension among gifted students. Self-perceived communication competence in the context of talking to acquaintances contributed negatively to the total variance in communication apprehension, while competence in public speaking contributed positively to the total variance in communication apprehension. No significant contribution was found in the contexts of talking to strangers or talking to friends. The researcher concluded with a set of recommendations and suggestions.